PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN DIVISI OPERASIONAL PADA PT SWADHARMA SARANA INFORMATIKA CABANG KEBON JERUK JAKARTA BARAT - Rupita, Ita; Suntari, Esti (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of leadership and the physical work environment on employee performance at PT Swadharma Sarana Informatika Kebon Jeruk branch either partially or simultaneously. The metHod used in this metHod is a quantitative approach, the population is 60 people by taking a saturated or total sample, namely a sample of 60 respondents. The research instrument has 30 statement items from the variables of leadership, physical work environment and employee performance. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, determination analysis and hypothesis testing. Based on the results of the analysis, the multiple regression value obtained is: Y= 24.747 + 0.436X1 The R value (correlation coefficient) is 0.651, meaning that the leadership variable (X1) and physical work environment (X2) Simultaneously has a strong relationship with the employee performance variable (Y). The R value (coefficient of determination) is 0.424 or 42.4% while the remaining 57.6% is influenced by other factors. Hypothesis testing obtained F valuecount > Ftable (20.954 > 3.150) this is also strengthened by the ikssation value of 0.000 < 0.05 so it can be concluded that H0 is rejected and H3 is accepted. It can be concluded that leadership (X1) and physical work environment (X2) simultaneously has an acceptable effect on employee performance (Y).